2022
DOI: 10.3389/fendo.2022.946327
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Regulated Apolipoproteins and Lipid Profiles as Novel Biomarkers for Polypoidal Choroidal Vasculopathy and Neovascular Age-Related Macular Degeneration

Abstract: Lipid dyshomeostasis has been implicated in the pathogenesis of various retinal and choroidal vascular diseases. This study aims to investigate whether apolipoprotein (apo) mediated differential regulation of lipid metabolism contributes to the phenotypes of polypoidal choroidal vasculopathy (PCV) and neovascular age-related macular degeneration (nAMD). This study involved 148 subjects including 53 patients with PCV, 44 patients with nAMD, and 51 age-, sex-matched subjects with normal fundus controls. Routine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…When group comparison between BRVO-and CRVO-affected eyes occurs, OR > 1 means the variable is an independent risk factor for the study eyes, and OR < 1 means the variable is a protecting factor for the study eyes. p < 0.05 indicated statistical significance [19].…”
Section: Discussionmentioning
confidence: 98%
“…When group comparison between BRVO-and CRVO-affected eyes occurs, OR > 1 means the variable is an independent risk factor for the study eyes, and OR < 1 means the variable is a protecting factor for the study eyes. p < 0.05 indicated statistical significance [19].…”
Section: Discussionmentioning
confidence: 98%
“…Osteosclerosis and osteoarthritis were observed in Ltbp-3 −/− mice. 50 Based on the previous hypothesis regarding the differential pathological mechanisms of PCV and nAMD, 51 , 52 we selected DCD and LTBP-3 as novel DEPs in these two groups for further validation. Although these novel DEPs were identified in both nAMD and PCV, the downregulation of DCD and LTBP-3 was not reproduced using the ELISA assay (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…However, many previous studies did not find a significant relationship between serum or plasma lipids and AMD, although several studies of larger size found a significant effect of high HDL on developing AMD [38,39]. In addition, it has been recently reported that ApoB/non-HDL-C is an independent risk factor for typical AMD, and apoB is an independent risk factor for PCV [40]. Low-density lipoprotein cholesterol is significantly higher in patients with PCV when compared with typical AMD [40].…”
Section: Serum or Plasma Cholesterol In Amdmentioning
confidence: 97%
“…In addition, it has been recently reported that ApoB/non-HDL-C is an independent risk factor for typical AMD, and apoB is an independent risk factor for PCV [40]. Low-density lipoprotein cholesterol is significantly higher in patients with PCV when compared with typical AMD [40]. Therefore, consideration should be given to the systemic diseases of AMD patients, and perhaps the results of medical examinations might be consulted.…”
Section: Serum or Plasma Cholesterol In Amdmentioning
confidence: 99%